Świadomość językowa młodzieży – próba pedagogicznego oglądu - Kuszak, Kinga (Studia Edukacyjne, 2025)
The article is theoretical in nature. It focuses on the language awareness among young people. Language awareness enables code-switching and balancing between the sociolect known as the youth language and the official, standard-compliant language. Depending on the context, language is used by young people to identify themselves with the group and to manifest their independence, distinctiveness and uniqueness. It also reflects their integration into linguistic norms and their creative transformation of these norms. The level of language awareness determines which variety young people choose to use in particular situations. Drawing on the levels of language awareness identified in the literature, the author presents examples of both low and high levels of language awareness in the linguistic competence of young people. The conclusion is presented within the context of the core curriculum, highlighting the need to correlate literary education with language education.